“It Will Ruin His Career”: Does Violence Against Women Really Damage the Careers of NBA Players? - Sailofsky, Daniel (Journal of interpersonal violence, 2022)
Arrests for acts of violence against women are a common occurrence for professional athletes, including National Basketball Association (NBA) players. Many sports fans, players, and those involved in professional sport believe that arrests for acts of violence against women, whether they result in a conviction or not, are highly detrimental to an athlete’s career. We matched all 30 NBA players arrested for acts of violence against women between 2000 and 2016 with similar players who were not arrested and examined the effects of the arrest on postarrest average annual salary and career longevity. We found no significant difference between arrested players’ careers and the careers of nonarrested counterparts. From a social learning perspective, this lack of punishment or loss of reward could be an important factor in continued acts of violence against women among NBA athletes.